Searching and Evaluating Publications and Preprints Using Europe PMC. Issue 3 (22nd March 2023) - Rosonovski, Summer; Levchenko, Maria; Ide‐Smith, Michele; Faulk, Lynne; Harrison, Melissa; McEntyre, Johanna
Abstract: In the field of life sciences there is a growing need for literature analysis tools that help scientists tackle information overload. Europe PubMed Central (Europe PMC), a partner of PubMed Central (PMC; National Library of Medicine, 2022), is an open access database of over 41 million life science publications and preprints, enriched with supporting data, reviews, protocols, and other relevant resources. Europe PMC is a trusted repository of choice for many life science funders (Europe PMC, 2022a), offering a suite of innovative search tools that allow users to search and evaluate the literature, including finding highly cited articles, preprints with community peer reviews, or papers referencing a proteomics dataset in the figure legend. In addition, Europe PMC utilizes text‐mining to help researchers identify key terms and find data and evidence in the literature. First‐time users often do not utilize the wealth of tools Europe PMC offers and can feel overwhelmed about how to perform the most effective search. This protocol, describing how to search and evaluate publications and preprints using Europe PMC, demonstrates how to carry out more efficient and effective literature searches using the tools provided by Europe PMC. This includes discovering the latest findings on a research topic, following research from a specific author, journal, or preprint server, exploring literature on a new method, expanding your reading list with relevant articles, as well as accessing and evaluating publications and preprints of interest. © 2023 EMBL‐EBI. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Finding articles and preprints on a topic of interest Basic Protocol 2 : Accessing an article Basic Protocol 3 : Browsing the article Basic Protocol 4 : Evaluating the article Basic Protocol 5 : Refining search results Basic Protocol 6 : Finding research by author Basic Protocol 7 : Finding a specific article Basic Protocol 8 : Finding information about a methodology Basic Protocol 9 : Finding evidence of biological interactions, relations, and modifications Basic Protocol 10 : Finding data behind a publication Basic Protocol 11 : Expanding a reading list and building a bibliography Basic Protocol 12 : Staying on top of the current literature